O CORPO CRISTÃO MIIDIÁTICO-DIGITAL: DESFRONTEIRIZAÇÃO DAS PRÁTICAS DE DIVULGAÇÃO RELIGIOSA MATERIALIZADAS NO YOUTUBE - SONIA GONÇALVES BATISTA DIAS (2024)
The general objective of this thesis is to analyze Christian religious discourse in digital media based on the proposal of the “crossing borders” thesis, a term we coined to propose an imaginary border between the discourse of dissemination and the discourse of loyalty. To this end, we revisit the studies of Silva (2020) in proposing three enunciative scenes referring to religious discourse (foundation, loyalty and dissemination). As a consequence of breaking this border, we propose mixing styles of discursive genres based on Zilberberguian miscegenation (2004). After the miscegenation, we analyze the discursive genres of this mixture in order to grasp the discursive body, manifested through the style, voice and character emanating from four actors of Christian enunciations in digital media, materialized, according to our proposal, in generic typologies of acting style. We analyze the Christian media-digital body, considering it as an organization inferred from the marks of the enunciated enunciation, supported by the syntactic and semantic components. This organization that we propose is to: situate, name, list, organize and classify through typologies. Therefore, the specific objectives of this thesis are to: a) analyze the body of the enunciator on the YouTube platform, considering it a discursive body, as pointed out by Discini (2012; 2015); b) analyze the body of the enunciator on the YouTube platform from the perspective of Zilberberguian miscegenation (2004); c) understand the style of the actors of Christian media enunciations, from a notion of style based on studies on the body in discursive semiotics; d) contribute to religious discourse studies in the discursive semiotics of today with regard to digital media; e) propose two enunciative scenes originating from the typology of Christian preaching in digital media; and to f) outline the phenomenon of crossing borders from a tensive perspective of miscegenation. The study methodology is qualitative and quantitative, with a survey of information and knowledge about research conducted in discursive semiotics in the field of religion and religiosity based on previously published works, placing different authors and data in dialogue. In addition, an analysis of the selected corpus with exploratory, descriptive and explanatory research is performed. The results obtained reveal distinct acting styles, which differ between some historically marked Catholic and Protestant practices and learned during the analysis of the chosen rhetorical arguments.